1989-90 National health survey. Accidents, Australia. - Australian Bureau of Statistics (Canberra : Australian Bureau of Statistics, 1992)
Contains national statistics indicating the level of illness/injury in the community resulting from accidents. Details of the place of occurrence and demographic and socio-economic characteristics of the persons involved are also provided.
Catalogue no. 4384.0.
Includes tables.
Keywords: Health surveys -- Australia; Accidents -- Australia -- Statistics; Health surveys -- Australia; Accidents -- Australia -- Statistics